Innovative Customer Relationship Management (CRM) Development in Marketplace: The Case Study of Tokopedia - Ajitrisna, Elingga (The Indonesian Journal of Computer Science, 2024)
This study examines Tokopedia’s innovative Customer Relationship Management (CRM) development in the Indonesian marketplace landscape, driven by technological advancements and shifting consumer behaviors. The research employs a two-pronged approach: data collection from Tokopedia's website and analysis using the McKinsey 7S Framework. Objectives include understanding Tokopedia's strategies to attract and retain customers through personalized marketing, customer feedback integration, and loyalty programs. The results indicate that Tokopedia's cohesive CRM approach, emphasizing shared values, leadership style, and skilled workforce, effectively enhances customer satisfaction and loyalty. This integrated strategy has contributed to Tokopedia's substantial growth and competitive edge in the dynamic marketplace ecosystem. Future research could explore Tokopedia's CRM effectiveness compared to competitors and the potential of targeted market segmentation strategies.